2022
DOI: 10.1021/acsaem.2c02116
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Supercapacitor Based on Advanced 2D Vanadium Disulfide/Black Phosphorus Hybrids for Wearable Electronics

Abstract: Vanadium disulfide−black phosphorus (VS 2 −BP) hybrids were synthesized by a one-pot hydrothermal-assisted method to achieve enhanced electrochemical activity for supercapacitor applications. The concentration of BP was optimized to prevent the restacking nature of VS 2 and to enrich the active edges for electrolytic ion intercalation. The charge storage kinetics of the best-performing VS 2 −BP as an active electrode has demonstrated the dominance of the pseudocapacitive nature of the material. Furthermore, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The resulting solution was diluted to 60 mL, placed in a Teflon-lined autoclave, and heated to 200 °C in a hot-air oven for 24 h. After being washed with distilled water and ethanol, the black product was dried overnight in a vacuum oven at 60 °C. 22 2.2. Material Characterization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting solution was diluted to 60 mL, placed in a Teflon-lined autoclave, and heated to 200 °C in a hot-air oven for 24 h. After being washed with distilled water and ethanol, the black product was dried overnight in a vacuum oven at 60 °C. 22 2.2. Material Characterization.…”
Section: Methodsmentioning
confidence: 99%
“…For the first time, Hao et al developed a flexible supercapacitor out of exfoliated BP. 21 Previously, our group demonstrated that forming heterostructures with BP improves the performance of pseudocapacitive 2D materials like VS 2 22 and conducting polymers such as PANI. 23 To exemplify, the addition of BP to VS 2 increased the number of electrochemical active sites, resulting in enhanced surface activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of BP can expand the number of active sites and increase the surface activity while avoiding stacking. 196 A charming cocktail effect produced by composite materials has attracted more interests to obtain satisfactory properties in different fields. By compounding with active materials to achieve a stable structure, the problem of volume expansion can be effectively reduced, and the synergistic effect between various materials can effectively increase the diffusion rate of ions.…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Sharma et al combined VS 2 with black phosphorus (BP) to form composite VS 2 /BP, which showed good electrochemical performance for supercapacitors. The presence of BP can expand the number of active sites and increase the surface activity while avoiding stacking …”
Section: Challenges and Solutionsmentioning
confidence: 99%